An Islamic Legal Review on Marriage Contract for Prospective Groom with Speech Impairment - Muhammad Shofwan Taufiq; Amelia Agil Fitri Yani (Faculty of Law Universitas Muhammadiyah Metro, 2025)
Acceptance of consent for mute speech is valid with the sign, if it can be understood, as is the case with a sale and purchase contract that is valid with the way of the sign, because the sign has a meaning that can be understood. But if one of the parties does not understand the signal, the consent is not valid, because the one who does the consent is only between the two people concerned. However, the issue of consent granted by mute-mute grooms can be done in several ways, including by sign, in writing or by way of representation. This research uses a juridical empirical approach. Sources and types of data in this study only use primary data and secondary data. Data collection in this study was carried out using literature and field studies. The analysis of the data obtained was carried out by means of qualitative analysis with an inductive mindset. The results of this study indicate an overview of Islamic law that marriages with speech impairments whose qabul use sign language in the form of hand and mouth movements that he understands the meaning of the contract, the marriage is considered valid provided that it fulfills the pillars and conditions of marriage. The practice of consent for marriage using sign language for persons with disabilities represented by expert guardians in Metro Timur District is the practice of consent for marriage done in sign language, which is spoken directly by the mute bridegroom, namely by using sign language, such as hand movements, head movements, eye blinks, statements of agreement and so on that can be understood in the majlis. The inhibiting factor in the implementation of the marriage contract for mutespoken grooms is the lack of sign language expert guardians who understand Islamic religion, especially in terms of the pillars and conditions of marriage. As well as the witness' lack of understanding about sign language, the witness was only given an understanding that the meaning of these gestures was like consent and acceptance under normal conditions